Coaching-based academic supervision to enhance teachers' pedagogical competence - Rini Susanti Gulo; Niswanto; Ismail; Nuri Handayani (Indonesian Journal of Educational Development (IJED), 2026)
Conventional academic supervision often remains administrative and less effective in supporting teacher growth. Coaching offers a reflective and collaborative alternative that empowers teachers through partnership and constructive feedback. This study investigates the construct of coaching-based academic supervision, identifies critical success factors, and analyzes its impact on teachers' pedagogical competence. A qualitative descriptive design involving a population of teachers and school principals from three public junior high schools in Simeulue Regency, with a sample of 15 participants selected through purposive sampling (three principals and twelve teachers), was employed. Data were collected through interviews, classroom observations, and document analysis, then analyzed using an interactive qualitative model consisting of three stages: data reduction, data display, and conclusion drawing. The findings revealed that coaching was implemented through three reflective and dialogic stages, namely pre-observation, observation, and post-observation. Its effectiveness was supported by teacher empowerment, collaborative leadership, a reflective culture, and openness to feedback, which led to improved lesson planning, innovative teaching strategies, and better classroom management. Based on these findings, it is recommended that schools institutionalize reflective coaching practices, provide continuous professional development for supervisors, and build a supportive school culture that fosters open dialogue and collaborative learning.